Water footprint of banana in the Brazilian semi-arid region - Rocha de Oliveira, Vandemberk (Revista Ciência Agronômica, 2023)
Due to water scarcity in semi-arid regions, water resources management strategies are indispensable for agricultural production, in order to guarantee food security for the population. Banana is of great importance in Brazilian agribusiness, with the Northeast region contributing the largest production, approximately 32% of national production. The objective of this study was to determine and evaluate the total water footprint of banana crop, considering the blue, green and gray water footprints, with a view to guiding water management in banana producing regions of the Brazilian semiarid region, in the State of Ceará, Brazil; in the Jaguaribe-Apodi and Tabuleiros de Russas Irrigation Projects, as well as a producing area in the municipality of Missão Velha. The average agricultural water footprint for Jaguaribe-Apodi, Tabuleiros de Russas and Missão Velha were 998.3; 1048 and 1107 m³ t-1, respectively. For Missão Velha, the blue water footprint was 780.9 m³ t-1 and for Jaguaribe-Apodi and Russas they were 830.6 and 862.7 m³ t-1, respectively. The regions studied showed similar blue water footprint, which demonstrates the need for water input from the crop and the dependence on surface and/or underground water sources. Water footprint assessment contributes to the decision-making of governments and producers regarding the real value of raw water, raising discussions related to raw water collection in the agricultural sector as well as the implantation and management of crops in the different hydrographic basins.